RFTS‐dependent negative regulation of Dnmt1 by nucleosome structure and histone tails. (11th September 2017) - Mishima, Yuichi; Brueckner, Laura; Takahashi, Saori; Kawakami, Toru; Arita, Kyohei; Oka, Shota; Otani, Junji; Hojo, Hironobu; Shirakawa, Masahiro; Shinohara, Akira; Watanabe, Mikio; Suetake, Isao
Abstract : DNA methylation in promoter regions represses gene expression and is copied over mitotic divisions by Dnmt1. Dnmt1 activity is regulated by its replication foci targeting sequence (RFTS) domain which masks the catalytic pocket. It has been shown that Dnmt1 activity on unmethylated DNA is inhibited in nucleosome cores. In the present study, we aimed to assess the effect of nuclesome formation on maintenance methylation at single CpG resolution. We show that Dnmt1 fully methylates naked linker DNA in dinucleosomes, whereas maintenance methylation was repressed at all CpG sites in nucleosome core particles. Deletion of RFTS partly released obstruction of Dnmt1 activity in core particles. Histone H3 tail peptides inhibited Dnmt1 in an RFTS‐dependent manner and repression was modulated by acetylation or methylation. We propose a novel function of RFTS to regulate Dnmt1 activity in nucleosomes. Abstract : Dnmt1 in full length or with a truncation of the 290 N‐terminal amino acids (Dnmt1 291) can methylate DNA in naked nucleosome linker regions but not in core particles. Dnmt1 602, in which the replication foci targeting sequence (RFTS) domain is deleted, gains access to nucleosome entry/exit sites. Furthermore, histone H3 tail peptides inhibit Dnmt1 in a RFTS‐dependent manner. We propose a novel function of the RFTS domain in regulating Dnmt1 activity in nucleosomes.